Public Perception of IKN as the Capital City of Indonesia After the Budget Blockage Issue through Mention and Sentiment Trend Analysis - Fitrianto, Mochamad Rizki; Sugiarto, Amalia Rizka (European Public & Social Innovation Review, 2025)
Introduction: IKN has become a concern for the Indonesian people both when it was a discourse and when it was implemented, even when the government changed. This study was conducted to examine the perception of the Indonesian people towards IKN. Methodology: This study is a qualitative descriptive study using the netnography method. The netnography method chosen is virtual ethnography, which is a type of research that focuses on social behavior in the digital realm via the internet. Result: Between January 24 and February 7, 2025, IKN received 10.7 thousand mentions with a reach of 110.1 million. Compared to the previous period (January 9-23, 2025), mentions decreased slightly (from 11.3 thousand), but the reach increased significantly (from 77.4 million). Positive sentiment remained stable at 4% of mentions, while negative sentiment rose from 10% to 12%. The peak of mentions occurred on February 3 (1.2 thousand mentions) and February 6 (1.1 thousand mentions), with February 6 also marking the highest daily reach of 22 million.